Water Treatment and Purification in Fiqh Perspective - et. al., Wan Ainaa Mardhiah Wan Zahari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Water is the primary source needed to ensure human and other creature life continuity. There are a lot of water on this planet, but increasingly this water is not where it is needed or it is of inadequate quality (purity) for human consumption or other beneficial for example industrial, agricultural and so on purposes. Contaminated water supply causing harm to human body health and also contributes to extinction to the certain creature. Thus, water-saving or wise water usage is an important matter in Islam. Reuse of wastewater or sewage water is a solution to the water crisis problem faced nowadays. The contaminated water is purified and treated by certain processes. Water purification or treatment water is introduced to produce pure and clean water. However, discussions and debates among experts and societies continue to occur because the water is categorised as pure water but not purify (musta'mal) and impure water and not purify (mutanajjis). Therefore, this study aims to identify the concept and method of water purification and treatment (تطهير الماء) according to Fiqh perspective. Methodology of this study is qualitative approach by using document analysis by analysing several classic Fiqh books by four mazhab (Hanafi, Maliki, Shafie and Hanbali). Hence, this study can discover the water purification method suggested in Fiqh perspective to be applied by Muslim communities in Malaysia.